2022
DOI: 10.1021/acs.jmedchem.2c01250
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Preclinical Safety Obstacles to Discover (S)-N-((1,2,3,5,6,7-Hexahydro-s-indacen-4-yl)carbamoyl)-6-(methylamino)-6,7-dihydro-5H-pyrazolo[5,1-b][1,3]oxazine-3-sulfonamide (GDC-2394): A Potent and Selective NLRP3 Inhibitor

Abstract: Inappropriate activation of the NLRP3 inflammasome has been implicated in multiple inflammatory and autoimmune diseases. Herein, we aimed to develop novel NLRP3 inhibitors that could minimize the risk of drug-induced liver injury. Lipophilic ligand efficiency was used as a guiding metric to identify a series of 6,7-dihydro-5H-pyrazolo­[5,1-b]­[1,3]­oxazinesulfonylureas. A leading compound from this series was advanced into safety studies in cynomolgus monkeys, and renal toxicity, due to compound precipitation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Of note, the 150‐mg starting dose in this study was anticipated to be subtherapeutic based on the prediction of human PK from preclinical studies, but the observed AUC was approximately three‐fold higher than the preclinical prediction and thus explains the discrepancy between the predicted and observed target coverage. Based on PK/PD modeling, the estimated plasma 90% inhibitory concentration (IC 90 ) value of ~1100 ng/mL (~2.5 μM) for IL‐1β and IL‐18 inhibition was in good agreement with the in vitro human whole blood IC 90 value (639 ng/mL, 1.48 μM) after correcting for the blood:plasma ratio of 0.6 9 . Based on the observed PDs and the estimated clinical IC 90 , twice‐daily dosing of 150 mg GDC‐2394 or greater is expected to provide at least 90% target inhibition in peripheral blood throughout the dosing interval.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Of note, the 150‐mg starting dose in this study was anticipated to be subtherapeutic based on the prediction of human PK from preclinical studies, but the observed AUC was approximately three‐fold higher than the preclinical prediction and thus explains the discrepancy between the predicted and observed target coverage. Based on PK/PD modeling, the estimated plasma 90% inhibitory concentration (IC 90 ) value of ~1100 ng/mL (~2.5 μM) for IL‐1β and IL‐18 inhibition was in good agreement with the in vitro human whole blood IC 90 value (639 ng/mL, 1.48 μM) after correcting for the blood:plasma ratio of 0.6 9 . Based on the observed PDs and the estimated clinical IC 90 , twice‐daily dosing of 150 mg GDC‐2394 or greater is expected to provide at least 90% target inhibition in peripheral blood throughout the dosing interval.…”
Section: Discussionmentioning
confidence: 69%
“…GDC‐2394 is an orally available, selective, and reversible small‐molecule inhibitor of NLRP3 9 . It selectively blocks IL‐1β and IL‐18 secretion following activation of the NLRP3 pathway by various stimuli, including cholesterol crystals, in biochemical and ex vivo cellular assays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, JT002 displayed good selectivity towards inhibiting NLRP3 in ammasome activation and did not interfere with either TLR4-mediated activation of the NF-κB pathway or other in ammasomes tested, such as NLRP1, NLRC4 or AIM2. Although the direct target of JT002 has not yet been identi ed, a recent publication that utilized cryo-EM demonstrated direct binding of a structurally similar compound to an allosteric pocket in the NACHT domain of NLRP3, thus explaining the in ammasome selectivity pro le 55 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings prompted the development of potent and selective NLRP3 inhibitors that are extensively used as pharmacological tools to elucidate possible clinical applications of NLRP3 targeting strategies. , In this rapidly expanding research field, numerous compounds are already under preclinical investigation, and few of them have reached phase I/II clinical trials. Among these, MCC950 ( 1 , Figure ) is the most studied NLRP3 inhibitor after its early discovery in 2003 . MCC950 was shown to block canonical and noncanonical NLRP3 activation at nanomolar concentrations in vitro with high selectivity over AIM2, NLRC4, or NLRP1 inflammasomes .…”
Section: Introductionmentioning
confidence: 99%